2018
DOI: 10.1016/j.jphs.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin I inhibits growth and invasion of cisplatin-resistant gastric cancer cells by partially inhibiting CIP2A/PP2A/Akt signaling axis

Abstract: The aberrant expression of cancerous inhibitor of protein phosphatase 2A (CIP2A) indicates poor prognosis and promotes EMT and metastasis. EMT, a crucial cellular process that occurs during cancer progression and metastasis, has been reported to promote drug resistance in several previous studies. Consequently, ongoing research has been focused on exploring therapeutic options for preventing EMT to delay or reverse drug resistance. Polyphyllin I (PPI) is a natural component extracted from Paris polyphylla that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Apart from being involved in cancer cell growth and apoptosis, CIP2A has also been found to play a role in chemoresistance of a variety of cancer cells. Recently, it has been found that inhibition of CIP2A enhanced the sensitivity to cisplatin in bladder cancer, gastric cancer, and ovarian cancer cells (Gao et al, ; Zhang et al, ; Li et al, ). In addition, the involvement of CIP2A in regulating metastatic process has also been evidenced.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being involved in cancer cell growth and apoptosis, CIP2A has also been found to play a role in chemoresistance of a variety of cancer cells. Recently, it has been found that inhibition of CIP2A enhanced the sensitivity to cisplatin in bladder cancer, gastric cancer, and ovarian cancer cells (Gao et al, ; Zhang et al, ; Li et al, ). In addition, the involvement of CIP2A in regulating metastatic process has also been evidenced.…”
Section: Discussionmentioning
confidence: 99%
“…CIP2A is a specific inhibitor of PP2A which is the most important tau phosphatase, and PPI can inhibit the expression of CIP2A protein in tumor 35,36 . To investigate whether PPI dephosphorylates tau by inhibiting CIP2A expression, the CIP2A and tau co‐transfected HEK293‐T cells were incubated with or without PPI (0.125, 0.25, 0.5, 1.0, or 2.0 μM) incubation for 48 hours and with or without PPI (0.5 μM) incubation for 6, 12, 24, 48, or 72 hours, and CIP2A expression, PP2A activity, and tau phosphorylation were detected.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Recently several labs have shown that PPI can inhibit tumor progression by inhibiting the expression of CIP2A. 35,36 Whether PPI can modulate the CIP2A expression thus ameliorating AD-related pathologic changes in AD is worthy exploration and identification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations